RUS Copernicus: an Expert Service for New Sentinel Data Users. Issue 1 (June 2020) - Guzzonato, E; Mora, B; Remondière, S; Palazzo, F
Abstract: With an unprecedented amount data acquired continuously, the Copernicus satellite constellations provide essential information for analysing and monitoring the Earth's surface and atmosphere. However, technical and knowledge barriers may affect user's uptake of such datasets. The Copernicus Research and User Support (RUS) Service (funded by the EC and managed by ESA) began operations in October 2017 and aims to support overcoming such issues. Provision of scalable, preconfigured cloud environments offers users the possibility to remotely store and process data. The platform relies on Free and Open-Source Software (FOSS). In addition, technical and scientific support (including training sessions) is provided to facilitate exploitation of Copernicus data. The RUS Service is specially addressed to users from European countries that are willing to discover and use Copernicus core products and datasets. The service is free for the eligible end users. Commercial and operational activities cannot be carried out through the RUS Service.